2013
DOI: 10.3109/14659891.2012.740138
|View full text |Cite
|
Sign up to set email alerts
|

“But no one told me it’s okay to not drink”: a qualitative study of young people who drink little or no alcohol

Abstract: Young people's drinking is a matter of social, media, and political concern and the focus of much policy activity within the United Kingdom. Little consideration has been given to the fact that some young people choose to drink little or not all and our knowledge and understanding of their choices and how they manage not drinking is limited. Nor has much attention been paid to the possibility that the insights of young light and non-drinkers could be useful when thinking about how to change the prevailing drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 14 publications
4
61
3
1
Order By: Relevance
“…Recently, the social experiences of non-drinkers have been described in UK research reports, providing evidence relating to young people's decision-making around alcohol use (Seaman & Ikegwuonu, 2010) and the processes of becoming and being a non-drinker (Herring, Bayley, & Hurcombe, 2013). These studies revealed that peer tolerance of nondrinking was maximised where individuals strategically deployed 'legitimate' reasons, whether dispositional (e.g., 'don't like the taste') or circumstantial (e.g., 'on medication', 'designated driver') in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the social experiences of non-drinkers have been described in UK research reports, providing evidence relating to young people's decision-making around alcohol use (Seaman & Ikegwuonu, 2010) and the processes of becoming and being a non-drinker (Herring, Bayley, & Hurcombe, 2013). These studies revealed that peer tolerance of nondrinking was maximised where individuals strategically deployed 'legitimate' reasons, whether dispositional (e.g., 'don't like the taste') or circumstantial (e.g., 'on medication', 'designated driver') in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies also emphasised the importance of dealing with the difficulties of non-drinking at a life stage where everyone seems to be drinking and in social environments where alcohol consumption is particularly prominent (e.g., parties, clubs). Evidence specific to non-drinkers has indicated diverse potential strategies for nondrinkers to use in social settings, including: rejecting stereotypical labels (e.g., 'boring'); adopting alternative identities; ensuring that drinkers do not feel judged; alleviating situational tension using humour; boundary-setting for being out; and being assertive or resolute in how non-drinking is spoken about (Herring et al, 2013). Notably, Seaman and Ikegwuonu (2010) found that non-drinkers expressed pride in their minority status.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of published studies focus specifically on round buying, but many of these are decades old (AIHW, 2011;e.g., Aitken, 1985;Barbara, Barnes, & Usher, 1978;Knibbe, Van De Goor, & Drop, 1993). The practice, however, is also referred to in qualitative studies of drinking (e.g., Herring, Bayley, & Hurcombe, 2014;Measham & Brain, 2005). Research on round buying identifies a number of themes, including the impact of round buying on relationships, social rules and expectations that govern round buying, and how overall consumption is affected (Aitken, 1985;Barbara et al, 1978;Knibbe et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Aitken (1985) suggests that heavier drinkers usually purchase rounds of alcohol, whereas light drinkers more often only purchase drinks for themselves. One strategy employed by light drinkers to circumvent heavy alcohol consumption is to avoid participating in round buying (Herring et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a las poblaciones estudiadas, la información proviene mayormente de personas con dependencia, ya en tratamiento o con recuperación natural (Amodeo & Kurtz, 1998;Carballo et al, 2014;Cunningham et al, 2005a;Harrison et al, 2014); de personas con un consumo excesivo que desearían cambiar su consumo o que lo hicieron (Cunningham et al, 2005a;Harrison et al, 2014;Matzger et al, 2005); y en menor medida de personas que se abstienen del consumo de alcohol (Epler et al, 2009), siendo que las razones por las cuales las personas se vuelven abstemias puede ser de importancia para entender cómo cambiar la cultura de consumo actual (Herring, Bayley, & Hurcombe, 2014).…”
Section: Introductionunclassified